Organizational Determinants of Ethical Dysfunctionality - Jurkiewicz, Carole L. (Journal of business ethics, 2016)
The literature on organizational ethicality to date has focused primarily on elements of the cultural, social, and political factors that enhance positive behaviors, interspersed with isolated accounts of malfeasance and wrongdoing. This treatise defines the anatomy of organizational dysfunction as a matter of ethicality, reframing the relationship from individual transgression to the organization itself. It is argued that the structure of an organization predisposes in large part whether it is itself conducive or prohibitive to unethical acts. Our approach allows for a new stream of ethics research whose focus is how an organization functions rather than on the specific acts of those within it.